G226(P) Circle: one way of developing international research practice. (27th April 2015) - Carter, B; Ford, K; Dickinson, A; Bray, L; Water, T; Arnott, J
Abstract : Aim: Researchers and academics face many research imperatives ranging from generating income, undertaking high quality research, writing 5 star papers, developing a national and international profile through to undertaking international research. None of this is easy. This presentation aims to explore and reflect on the process and successes achieved so far by the founding members of a community of research practice – Circle. Methods: Although perhaps not an obvious academic setting, Circle was developed whilst walking. Many good ideas emerge when friends and colleagues are given the chance to meet, talk, breathe and reflect. We walked and talked across parts of Tasmania, New Zealand and the UK; these walks were separated by months, geography and competing commitments. The initial three walker-researchers co-opted colleagues also working with children and families into a group that would eventually become Circle. Together we mapped our research interests and the research priorities of our home institutions and countries and started to identify research topics which would mean that our international efforts would meet various performance objectives. We discussed funding opportunities and thought about creative ways of building sound international research based on modest resources. We identified ways in which we could capitalise on each others' strengths and expertise. We also identified ways of building strong co-authorship based on our joint research and common interests. Results: From tentative steps we have created a robust and growing Circle of researchers who are working together, providing advice, support and mentorship. Measureable achievements include publication of a textbook on nursing children, co-authored papers and co-presented papers, international supervision of research students, development of a website and completion of an international photo-elicitation study. Conclusion: Opportunities exist for international work but these require innovative thinking. Sharing ideas and supporting each other has widened and deepened our thinking about research and practice and created a sense of camaraderie. And we continue to walk together whenever we get a chance.